Tunable Aminooxy‐Functionalized Monolayer‐Protected Gold Clusters for Nonpolar and Aqueous Oximation Reactions. (30th May 2019) - Sibakoti, Tirtha R.; Stinger, Colton R.; Adhihetty, Prasadanie K.; Zamborini, Francis P.; Nantz, Michael H.
Abstract: Aminooxy (–ONH2 ) groups are well known for their chemoselective reactions with carbonyl compounds, specifically aldehydes and ketones. The versatility of aminooxy chemistry has proven to be an attractive feature that continues to stimulate new applications. This work describes application of aminooxy click chemistry on the surface of gold nanoparticles. A trifunctional amine‐containing aminooxy alkane thiol ligand for use in the functionalization of gold monolayer‐protected clusters (Au MPCs) is presented. Diethanolamine is readily transformed into an organic‐soluble aminooxy thiol (AOT ) ligand using a short synthetic path. The synthesizedAOT ligand is coated on ≤2‐nm‐diameter hexanethiolate‐(C6 S)‐capped Au MPCs using a ligand‐exchange protocol to afford organic‐solubleAOT /C6 S (1:1 ratio) Au mixed monolayer‐protected clusters (MMPCs). The synthesis of these Au(C6 S)(AOT ) MMPCs and representative oximation reactions with various types of aldehyde‐containing molecules is described, highlighting the ease and versatility of the chemistry and how amine protonation can be used to switch solubility characteristics. Abstract : Click chemistry on the surface of Au monolayer‐protected clusters (MPCs) is demonstrated by using a solubility‐switchable trifunctional amine‐containing aminooxy alkanethiol. The ligand is incorporated onto <2‐nm‐diameter Au MPCs and subsequently reacted with aldehyde‐functionalized molecules with diverse properties. Versatile oximation reactions on Au clusters with potential applications in sensing, separations, and catalysis are highlighted.